Efeito de Bacillus thuringiensis e produtos fitossanitários sintéticos na longevidade de operárias Apis mellifera L. (Hymenoptera: Apidae) - Libardoni, Gabriela (2017)
Africanized bees (Apis mellifera L.) are disappearing and are believed to be due to the intense use of insecticides, pollution and climate change, however many crops depend on the pollination performed by these bees. The objective of this work was to evaluate the effect of three strains of Bacillus thuringiensis (Bt) (IPS 82, BR 81 and BR 147), entomopathogen used for the control of Acetamiprid + Alpha-cypermethrin, PFS 2: Imidacloporide + Beta-Cyflutin and PFS 3: Fenitrothione + Esfenvalerate), on the longevity of African female A. mellifera workers. Three bioassays were performed with the Bt and PFS lines: A) Spraying on A. mellifera; B) A. mellifera contact with pulverized surface and C) Candi paste incorporated with the products and histological analysis of the medium intestine of the bees. In the three bioassays the control was composed of sterilized deionized water. Each treatment consisted of 60 bees, each bee being considered a repetition. The bioassays were maintained in a BOD type chamber (34 ± 2ºC, 60 ± 5% U.R) and the workers longevity was evaluated at one; two; three; four; five; six; nine; 12; 13; 18; 21; 24; 30; 36; 42; 48; 60; 72; 96; And 120 hours. In Bt spraying on A. mellifera, it was verified that only the Bt 1 strain (IPS 82) caused a reduction in worker longevity (88.7 hours), while in the contact bioassay the Bt 3 - BR147 strain caused a reduction (101, 2 hours). All strains of Bt evaluated when incorporated into A. mellifera feed reduced workers longevity (Bt 1 - IPS 82: 64.50 hours; Bt 2 - BR 81: 64.56 hours and Bt 3 - BR 147: 60). And the histological analysis showed the disintegration of the epithelial cells of the bees mesentery, caused by the bacteria they ingested. The three synthetic phytosanitary products reduced the longevity of A. mellifera workers in the direct spray bioassay (PFS 1 and PFS 2 - 1.0 hour; PFS 3 - 2.21 hours). At the contact of A. mellifera with a PFS-sprayed surface, the bees stayed two hours in contact with the products on the petri dish, and at the end of these two hours, 100% bees that came in contact with the three synthetic phytosanitary products were dead. When the PSFs were incorporated in the diet, they reduced the longevity of the workers (PFS 1 - 22 hours, PFS 2 - 21.72 hours and PFS 3 - 43.93 hours) and in the histological analysis it was possible to observe differences in the workers from A. mellifera fed with the three PFSs. although the Bt lineages reduce the longevity of A. mellifera workers, it is not possible to assert that they are not selective, since the interference is minimal when compared to interference caused by PFSs, which caused a drastic reduction in the longevity of A. mellifera.